Effectiveness of a Preseason Prevention Program on Arm Injury Risk Factors: An Randomized Control Trial in Adolescent Pitchers. Issue 3 (24th March 2016) - Thigpen, Charles A.; Bailey, Lane Brooks; Kissenberth, Michael J.; Noonan, Thomas J.; Hawkins, Richard J.; Shanley, Ellen
Objectives: Deficits in posterior shoulder flexibility and strength have been identified as modifiable risk factors for pitching injuries. There are no studies showing the effect of a prevention program on arm injuries and associated risk factors such as strength and ROM. The purpose of this study was to assess the effectiveness of a preseason prevention program to resolve these deficits in adolescent pitchers. Methods: Baseball pitchers (n=143 age=15.7±1.2; height=165.0±43.8cm; weight=72.2±12.6kg) participating in all team activities were block randomized by school to intervention (INV n=88) or control (CON n=76) groups. The INV group received an Athletic Trainer supervised posterior shoulder flexibility and strengthening program (3x/week for 8-weeks). The CON group participated in their usual training. All pitchers participated in a 4-week interval-throwing program immediate to the start of practice. Bilateral shoulder ROM and strength were assessed pre-post program using a digital inclinometer (DI) to measure supine external rotation(ER), internal rotation (IR), and horizontal adduction (HA) ROM with the scapula stabilized at 90 degrees of abduction. Standard manual muscle testing was used for strength assessments using a hand held dynamometer with arm at the side(ER-0) and in supine 90 degrees/90 degrees (ER-90, IR-90) then normalized to body weight (BW). Injuries were recorded over the subsequent baseball season. Two trials were averaged and used to calculate deficits (non-dominant-dominant) and pre-post change scores to examine the ability of the program to ameliorate baseline deficits associated with injury risk. A one-way ANOVA was used to compare change scores between groups and a 2-way ANOVA (group by injury) to examine the change scores influence on injury (α=0.05). Results: The INV group displayed a greater reduction in IR deficit(INV=7.3 degrees ±11;CON=1.8 degrees ±9;F(1, 106)=5.1, P=0.01) P=0.05) and HA deficit(INV=3.3 degrees ±13; CON= -2.4 degrees ±11;F(1, 106)=6.7, P=0.01) compared to the CON group. The INV group also maintained their dominant ER-0: IR-90 ratio (INT=-1.6 ±5%BW; CON= -3.5 ±5%BW; F (1, 106) =2.1, P=0.09) compared to the CON group. There were 19 arm injuries over the subsequent season (INV=11; CON=8 arm injuries). Control group pitchers who went on to suffer an injury did not decrease their HA deficit (Uninjured=3.0 degrees ±10;Injured=-9.5 degrees ±14;F(1, 106)=3.3, P=0.03) or their IR deficit went on to suffer an injury(Uninjured=-1.7 degrees ±8;Injured 8.5 degrees ±13;F(1, 106)=3.8, P=0.02). There were no other differences between or among groups (P>0.05). Conclusion: Adolescent pitchers displayed clinically meaningful improvements in posterior shoulder flexibility (HA and IR) and maintenance of their ER: IR ratio during an Athletic Trainer supervised preseason program. The improvements in HA and IR deficits were associated with decreased injury risk over the course of the subsequent high school season. Thus, a targeted pre-season program appears to be effective in improving HA deficit and impacting injury risk. Further studies are warranted to confirm our results.